(untitled) (Singaporean Journal of Business Economics and Management, 2016)
The purpose of this paper is to highlight the impact of globalization on Nigeria manufacturing sector. Specifically, the study aimed to pursue the following objectives: to evaluate the impact of trade liberalization on the consumption of Nigeria made products, to determine the impact of technology on product quality in the Nigeria manufacturing industry, to ascertain the effect of globalization on employee job relations in the Nigeria manufacturing industry. The study had a population size of 640, out of which a sample size of 246 was realized using Taro Yamane Formula at 5% error to tolerance and 95% level of confidence. The instrument used for data collection was primarily questionnaire and interview. The total numbers of 246 copies of the questionnaire were distributed while 230 copies were returned. The descriptive research design was adopted for the study. Three hypotheses were tested using linear regression statistical tool. The findings indicate that trade liberalization has significant negative impact on the consumption of Nigeria made products ( r = 0.893 > r = 0.544 ; te 29.976 > t_t = 4.321 p < 0.05 . Technology has a positive impact on product quality in the Nigeria manufacturing industry ( r = 0.718 > r = 0.544 ; t_c = 5.591 > t_t = 4.321 p < 0.05 ). Globalization has significant positive effect on employee job relations in the manufacturing industry ( r = 0.909 > r = 0.544 t_c = 33.223 > t_c = 4.321 p < 0.05 . The study concluded that globalization is a sword of double edge that promotes and demote economic activities of any developing nation. The study recommends that government should reposition its policies in order to monitor the activities of these agents of globalization as it affects our manufacturing sector.